2,4-DICHLORPHENOXICACETIC ACID AT LOW CONCENTRATIONS ENHANCES REPRODUCTIVE ABILITY AND OXIDATIVE STRESS RESISTANCE OF YEAST SACCHAROMYCES CEREVISIAE - Maria Bayliak; Nadia Burdylyuk (Vasyl Stefanyk Precarpathian National University, 2015)
2,4-dichlorphenoxicacetic acid (2,4-D) is one of the most widely used herbicides with well documented toxic effects on non-target organisms. In this study, the effect of low concentrations of 2,4-D on reproductive activity and resistance of yeast S. cerevisiae to oxidative stress was evaluated. Supplementation of the cultivation medium with 0.1-100 µM 2,4-D did not affect the rate of yeast growth. In early stationary phase, yeast cultures grown with 0.1 and 1 µM 2,4-D had higher number of reproductively active cells than control ones (without 2,4-D). In exponential phase, S. cerevisiae cells grown in the presence of 1-100 µM 2,4-D were more resistant to hydrogen peroxide comparing to control ones. Thus, the herbicide increased reproductive potential and cross-resistance to oxidative stress in yeast but the effective concentrations of 2,4-D were different for these phenomena. In summary, the results suggest possible involvement of certain hormetic mechanisms in the influence of 2,4-D at low concentrations on yeast.